Pinus pinea above ground biomass estimation with very high spatial resolution satellite images - Gonçalves A.C.; Sousa A.M.O.; Silva J.R.M. (Mediterranean pine nuts from forests and plantations, 2017)
Above ground biomass is frequently estimated with forest inventory data and an extrapolation method for the per unit area evaluations. This procedure is labour demanding and costly. In this study above ground biomass functions, with crown horizontal projection as the independent variable, were developed. Multi-resolution segmentation method and object-oriented classification based on very high spatial resolution satellite images, were used to obtain the area of tree crown horizontal projection for Pinus pinea L. A set of inventory plots were measured and with existing allometric functions for this specie above ground biomass per tree and per plot were calculated. The two data sets were used to fit linear functions to estimate above ground biomass for individual plot and for their cumulative values. The results show a good performance of the models. Errors smaller than 10%, correspond to stand areas greater than 1.4 ha. These functions have the advantages of estimating above ground biomass for all the area under study or surveillance, not requiring forest inventory; allowing monitoring in short time periods and easily implemented in a geographical information system environment.
2. International Meeting on Mediterranean Stone Pine for Agroforestry : AgroPine2016, 2016/05/18-20, Oeiras (Portugal)